TEACHER HUMAN RESOURCE MANAGEMENT BASED ON ISLAMIC EDUCATIONAL PRINCIPLES - -, Findi Alexsandy; Mulyawan Safwandy Nugraha (Leadership:Jurnal Mahasiswa Manajemen Pendidikan Islam, 2025)
This study aims to analyze the management of teacher human resources based on the core principles of Islamic Educational Management at Madrasah Ibtidaiyah Maarif Daarut Taqwa, Cibatu Garut. The research focuses on six key components of human resource management: planning, recruitment and selection, teacher development, performance appraisal, reward systems, and work discipline and ethics. A qualitative case study approach was employed, using interviews, observations, document analysis, and Likert-scale questionnaires to obtain comprehensive empirical data. The findings indicate that all aspects of teacher human resource management fall within the good to very good categories. Islamic work culture, the exemplary leadership of the principal, and the integration of amanah and ihsan values emerge as the most influential factors supporting the effectiveness of the management system. Nevertheless, several areas still require improvement, particularly the consistency of annual teacher workforce planning and the development of a competency-based promotion system. This study highlights that Islamic spiritual values function not only as ethical foundations but also as strategic frameworks in managing teachers within Islamic educational institutions. The results contribute to strengthening theoretical perspectives in Islamic Educational Management and offer practical recommendations for madrasahs to build a more integrated, value-based, and sustainable human resource management model. Keywords: Islamic Educational Management; Teachers; Human Resources; Madrasah; Islamic Values. Abstrak Penelitian ini bertujuan untuk menganalisis pengelolaan sumber daya manusia guru berbasis prinsip Manajemen Pendidikan Islam di Madrasah Ibtidaiyah Maarif Daarut Taqwa Cibatu Garut. Fokus penelitian diarahkan pada enam komponen inti pengelolaan SDM, yaitu perencanaan, rekrutmen dan seleksi, pembinaan dan pengembangan, penilaian kinerja, sistem penghargaan, serta disiplin dan etika kerja guru. Penelitian menggunakan pendekatan kualitatif dengan desain studi kasus melalui wawancara, observasi, dokumentasi, dan kuesioner skala Likert sebagai instrumen pendukung. Hasil penelitian menunjukkan bahwa seluruh aspek pengelolaan SDM guru berada pada kategori baik hingga sangat baik. Budaya kerja Islami, keteladanan kepala madrasah, dan integrasi nilai amanah serta ihsan menjadi faktor dominan yang memperkuat kualitas manajerial madrasah. Namun, beberapa aspek masih memerlukan penguatan, terutama dalam perencanaan kebutuhan guru secara rutin dan pengembangan sistem promosi berbasis kompetensi. Penelitian ini menegaskan bahwa nilai-nilai spiritual Islam tidak hanya menjadi landasan etik, tetapi juga kerangka kerja strategis dalam pengelolaan SDM guru. Temuan ini memberikan implikasi penting bagi penguatan teori Manajemen Pendidikan Islam sekaligus menyediakan rekomendasi praktis bagi madrasah untuk mengembangkan model pengelolaan SDM yang lebih terintegrasi dan berkelanjutan. Kata Kunci: Manajemen Pendidikan Islam; Guru; Sumber Daya Manusia; Madrasah; Nilai Islam.